Propaganda dotycząca Ziem Zachodnich i Północnych Polski w prasie krajowej 1945 roku = Propaganda on Poland's western and northem territories by the national press in 1945 - Domke, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper focuses on the Polish national press' propaganda on the so-called "Recovered Territories" which peaked in the year 1945, when the fate of those territories was decided and the Polish local administration established - first, as ir were, in a self-styled way (over the period of Febntary- July) and then, after the Potsdam Conference, formally (August-December).
Keywords: Ziemie Zachodnie i Północne; Polska - historia - od 1944 r.; propaganda komunistyczna; prasa polska